Virtual realities : International Dagstuhl Seminar, Dagstuhl Castle, Germany, June 9-14, 2013, Revised selected papers /: International Dagstuhl Seminar, Dagstuhl Castle, Germany, June 9-14, 2013, Revised selected papers. (2015) - Unknown
No abstract available